Influence of electrodes area ratios and the discharge volume in RF capacitively coupled plasma - Ahmad, Moyad Abdullah (Iraqi Journal of Physics, 2019)
Experimental results on harmonic distortions in 13.56 MHz RF Argon glow discharge using different grounded electrodes areas and electrodes spacing are presented. The experiment is carried out at four pressure values. RF power values used are between 20 and 90 watts. The results indicate significant increase in distortions at two specific values of the cone angle enclosing the two electrodes within its geometrical volume. The computation of the cone head angle gave the symmetry discharge or asymmetry as well as when the angle is small the condition is near symmetry discharge associated with decrease in the nonlinearity.